الحاجات الارشادية لأمهات اطفال اضطراب التوحد من وجهة نظرهم دراسة ميدانية بمركز البيداغوجي للمعاقيين ذهنيا2 بولاية الأغواط - مزاري فاتن; زنبط مريم; خنفار سامرة (My University, 2023)
The current study aimed to identify the most prominent counseling needs for mothers of autistic children in the state of Laghouat in the light of some variables (the mother's profession، the mother's scientific qualification، the economic level of the mother)، following the descriptive approach، and the researchers have prepared a questionnaire for the counseling needs of mothers of autistic children، consisting of (28) items divided into two dimensions: After the psychological and social needs and after the educational cognitive needs، then the researchers applied it to a sample of (30) mothers of children with autism disorder has been treated The data in the SPSS program followed the following statistical methods: arithmetic averages and standard deviations The results indicated that the counseling needs of mothers of children with autism disorder were all high and the need for knowledge and education came in first place . The results of the study also resulted in no statistically significant differences in the guidance needs of mothers of children with autism disorder due to each of the variables. (the educational level of the mother، the professional status of the mother) and the existence of statistically significant differences for the guidance needs due to the variable of the mother's professional status. Through the results of the study، the researchers reached a set of suggestions and recommendations. Keywords: counseling needs، autism disorder، mothers of autistic children